Studies on nanoprotein vaccine alleviating symptoms of mice allergic to rFel d 1 - Mai, Yanqi; Sun, Xiaozheng; Liu, Xiaoxuan; Chen, Huricha; Liang, Xinglan; Huang, Ying; Wu, Xiaojuan; Wei, Shuangshuang; Wang, Dayong; Pei, Yechun (Frontiers in Immunology, 2025)
IntroductionGlobally, cat allergens are a common cause of allergic rhinitis and asthma. Fel d 1 is the primary allergen among cat allergens and can induce a broad range of allergies through airborne transmission.MethodsIn our study, we constructed layered double hydroxide (LDH) nanoparticles loaded with PADRE-rFel d 1, aiming to address allergies triggered by Fel d 1. We utilized a mouse model sensitized with purified rFel d 1 and then immunized them subcutaneously with LDH nanoparticles loaded with PADRE-rFel d 1.ResultsOur results indicated that this nanoparticle vaccine effectively restored the balance of Th1/Th2 and Th17/ Treg cells, which led to a reduction in inflammatory cell infiltration, mitigated local and systemic stress responses induced by rFel d 1, decreased airway hyperresponsiveness, and lowered serum IgE levels.DiscussionConsequently, the LDH loaded with PADRE-rFel d 1 vaccine shows promise as an effective treatment for cat allergies.